Production Characteristics and Optimization of Mitigation Mussel Culture - Taylor, Daniel; Saurel, Camille; Nielsen, Pernille; Petersen, Jens Kjerulf (Frontiers in Marine Science, 2019)
Bivalve environmental services have become a focal point for their inherent role in the management of eutrophication, while active cultivation has become increasingly acknowledged as a mechanism for integrated nutrient reduction. In recent years, cultivation practices designed specifically for nutrient extraction have emerged; ‘mitigation culture’. While modeling efforts have been able to describe expanded potential of these services, only a single commercial pilot scale, real-world demonstration, has been documented. Over two production seasons (2017-2018), the optimization of nutrient extractive potential of mussels (Mytilus edulis) at full commercial-scale was evaluated by first testing multiple density configurations of conventional longline-spat collector setups and potential harvest times, then by comparing different cultivation technologies at three farms. Potential biomass volumes of 770-1700 t with longlines and 2100-2600 t on nets was demonstrated in full-scale production (18.8 ha), yielding 0.6-1.27 t N ha-1 and 0.04-0.1 t P ha-1, and 1.63-2.0 t N ha-1 and 0.1-0.12 t P ha-1 respectively. In general, 1 t of harvested mitigation mussels will yield 13.7 kg N and 0.9 kg P. Winter harvests exhibited higher yields (103-124%) than early spring harvests on optimized configurations, favoring an abbreviated production season. Production potential was similar between sites, despite differing environmental conditions, indicating eutrophic waters are suitable for expanded mitigation production. This study presents for the first-time production data of mitigation mussels utilizing different configurations and technologies to maximize yield and nutrient extraction potential.